Switzerland : Technical Note-Stress Testing the Banking System. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Note on Stress Testing the Banking System on Switzerland summarizes the stress tests undertaken for the Swiss banking system as part of the 2013 Financial Sector Assessment Program (FSAP) Update. The objective of this exercise has been to assess the resilience of the banking system to major macroeconomic shocks and sources of risk. The stress tests focused on the banking system and covered almost the entire banking system. Systemic banks should continue the front-loaded build-up in capital buffers, which has contributed to their resilience to shocks. The results suggest that the two large banks should continue the front-loaded build-up in capital buffers, which has contributed to their resilience to shocks. Stress tests results for the two large systemic banks are sensitive to the definition of capital. Stress tests results suggest that banks in other banking categories are well capitalized. Notwithstanding important data limitations and relying on broad assumptions based on aggregate and partial information, stress tests show that capital ratios remain broadly adequate for most banks under all scenarios.